Nikah Muda: The Hijrah Movement of Anti-Dating Communities from Progressive to Conservative in Indonesia (A Critical Study of Hadith) - Rahman, Rahman; Ilyas, Ilyas; Alwi, Zulfahmi; Zailani, Zailani (Millah: Journal of Religious Studies, 2024)
The proliferation of hijrah groups among youth has had a significant impact, with positive outcomes such as enhanced religious understanding among teenagers and an increase in the adoption of more Islamic attire. However, this has also brought about negative consequences, including the dissemination of radical and textual interpretations, leading to conservatism. This article aims to uncover the controversy surrounding early marriage among Muslim millennials, driven by a tendency towards textual religious understanding. The research employs a qualitative method, drawing primary data from social media platforms of anti-dating millennial communities and online Islamic organizations in Indonesia. Secondary data were sourced from books, journals, and other relevant articles. The research findings indicate that controversy arises from the selection of hadith texts and differing interpretation methods. Anti-dating communities use motivational hadiths to support early marriage, employing a literal textual understanding related to sexual motivation, religious and individual piety, the vision of a happy family, emulation of the Prophet's marriage, and assurance of sustenance from Allah. Conversely, scholars use hadiths to reject early marriages with contextual understanding. The disregard of the youth for the views of scholars opposing early marriage indicates a shift in religious authority among Muslim millennials from traditional figures to influencers popular on social media. Early marriage reflects the hybridization of the religious identity of Muslim millennials, maintaining religious values while remaining trendy and cool. The re-reading of hadiths is conducted by examining the social-historical context and contemporary circumstances within the discourse of modernity.